The effectiveness of Jamblang (Syzygium cumini (L) Skeels) extract on the atherogenic index in a diabetic rat model - Mulyati Sri Rahayu; Nurfardian Nurfardian; Ayu Nanda Sari (AcTion: Aceh Nutrition Journal, 2023)
Jamblang fruits (Syzygium cumini (L.) Skeels) have the potential as an antioxidant by facilitating glucose and lipid metabolism for reducing the atherogenic index (AI). This study aimed to explore the effect of the Jamblang extract on the atherogenic index in a diabetic rat model. This pre- and post-control group design study was conducted in the Pharmacology Laboratory of Universitas Sumatera Utara. Twenty-five rats were divided into five groups. Alloxan 120 mg/kg BW was administrated intraperitoneally, and the rats' fasting blood glucose levels were measured four days later. Group I (negative control) were treated with aqua dest, group II (positive control) was treated with glibenclamide 1,25 mg /kg BW, and group III, IV, and V were given an extract of Jamblang at a dose of 125, 250, and 500 mg/kg BW for seven days. Trigliserida and HDL-C measured using spektrofotometer microlab. The data were subjected to the Kruskal-Wallis test to examine the effect of Jamblang extract in different doses on the atherogenic index, followed by a Mann- Whitney Post hoc test. The result revealed that the extract Jamblang dose of 125, 250, and 500 mg/kg BW significantly decreased the atherogenic index (p value= 0,012<0,05). In conclusion, the Jamblang (Syzygium cumini (L.) Skeels) with the best-tested dose was 500 mg/kgBW to decrease the atherogenic index until 0,42 in vivo study.